Penerapan Linear Programming dalam Optimasi Perencanaan Produksi Industri Kecil Menengah di Indonesia: Studi Sistematis dan Meta-Analisis - Vaniloran Elysa Andriani (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Abstract Small and Medium Industries (SMIs) play a strategic role in Indonesia’s economy, yet many still face challenges in production efficiency and profit maximization. Linear Programming (LP) has been proven to be an effective optimization method for addressing production planning problems. This study aims to conduct a systematic literature review of the application of Linear Programming in Indonesian SMIs over the period 2018–2025, in order to identify the methods employed, the industrial sectors investigated, and the impact of their implementation on profit improvement. Using a Systematic Literature Review (SLR) approach guided by the PRISMA framework, 53 selected articles were examined in depth and synthesized through meta-analysis. The findings indicate that the Simplex method dominates usage (60.38%), followed by Goal Programming (13.21%) and Fuzzy Linear Programming (11.32%). The food and beverage sector constitutes the most frequently studied industrial sector (71.70%). Meta-analysis of 42 studies reporting quantitative data shows an average profit increase of 18.73%, with a range from 3.85% to 52.17%. Factors influencing the magnitude of improvement include the type of optimization method applied, the complexity of production constraints, and the initial level of capacity utilization. This study provides a theoretical contribution to understanding patterns of LP implementation in Indonesian SMIs and offers practical implications for practitioners and policymakers in adopting optimization technologies to enhance the competitiveness of the national SMI sector. Keywords: Linear Programming, Production Optimization, Small and Medium Industries, Systematic Literature Review, Meta-Analysis, Indonesia Abstrak Industri Kecil Menengah (IKM) memiliki peran strategis dalam perekonomian Indonesia, namun banyak yang masih menghadapi kendala dalam efisiensi produksi dan maksimalisasi keuntungan. Linear Programming (LP) telah terbukti sebagai metode optimasi yang efektif untuk mengatasi permasalahan perencanaan produksi. Penelitian ini bertujuan melakukan kajian literatur sistematik terhadap penerapan LP pada IKM di Indonesia periode 2018-2025 untuk mengidentifikasi metode yang digunakan, sektor industri yang diteliti, dan dampak implementasinya terhadap peningkatan keuntungan. Menggunakan pendekatan Systematic Literature Review (SLR) dengan framework PRISMA, sebanyak 53 artikel terpilih dianalisis secara mendalam melalui meta-analisis. Hasil penelitian menunjukkan bahwa metode Simpleks mendominasi penggunaan (60,38%), diikuti Goal Programming (13,21%), dan Fuzzy Linear Programming (11,32%). Sektor industri makanan dan minuman merupakan objek penelitian terbanyak (71,70%). Meta-analisis terhadap 42 studi yang menyajikan data kuantitatif menunjukkan rata-rata peningkatan keuntungan sebesar 18,73% dengan rentang 3,85% hingga 52,17%. Faktor-faktor yang mempengaruhi tingkat peningkatan meliputi jenis metode optimasi, kompleksitas kendala produksi, dan tingkat utilisasi kapasitas awal. Penelitian ini memberikan kontribusi teoritis dalam memahami pola penerapan LP pada IKM Indonesia serta implikasi praktis bagi pelaku usaha dan pembuat kebijakan dalam mengadopsi teknologi optimasi untuk meningkatkan daya saing IKM nasional. Kata Kunci: Linear Programming, Optimasi Produksi, Industri Kecil Menengah, Systematic Literature Review, Meta-Analisis, Indonesia